Pemanfaatan Daun Sidr (Ziziphus spina-christi L.) untuk Menstimulasi Pertumbuhan Rambut: Studi Eksperimental pada Tikus Putih Jantan - Elfasyari, Trie Yuni; Herlina, Merlin; Trisna, Mevy (Herbal Medicine Journal, 2025)
Sidr leaves (Ziziphus spina-christi L.) contain bioactive compounds such as flavonoids, saponins, tannins, phenolics, and alkaloids, that have the potential to stimaulate hair growth. However, scientific studies investigating the use of Sidr leaves as a hair growth-promoting agent remain limited. This study aims to scientifically evaluate the effectiveness of ethanol extract of sidr leaves (EEDS) on hair growth through an in vivo using male white rats (Rattus norvegicus). EEDS was applied topically in concentrations of 1%, 3%, and 5%. Hair length was measured using a caliper every 5 days for 15 days. The weight of the hair was measured on day 15 by shaving the hair of each group of rats. The results showed that EEDS at a 5% concentration effectively promoted hair growth in rats. However, there is no significant relationship between hair length and hair weight of the rats